Gender-Specific Non-Disclosure of Mental Distress - Anna Wagner; Doreen Reifegerste (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
Research suggests that non-disclosure of mental distress is associated with poorer mental health. While men are more reluctant to communicate about personal issues with informal and professional social contacts, little is known about the reasons for and factors associated with non-disclosure among men and women. Based on the Disclosure Decision-Making Model and the Communication Privacy Management Theory, we conducted a cross-sectional online survey with a quota sample of 2,471 participants in Germany. In the study, we (a) examined gender differences regarding non-disclosure of distress, (b) aimed to identify individual and relational factors associated with non-disclosure for both genders, and (c) studied men's and women's reasoning for non-disclosure of mental distress. Findings demonstrate that (a) non-disclosure was not higher in the male subsample but men had less trusted contacts; (b) individual level factors, particularly the conformity to traditional gender norms, were associated with non-disclosure among both genders; (c) men stipulated the superficiality of the relationship as more relevant reasons, while women indicated privacy and feelings of shame/self-blame as more important. The study findings might inform gender-sensitive mental health campaigns in the sense that questioning traditional gender norms could contribute to disclosure of mental distress among both men and women.